Sedimentary layers identification of Bribin underground river in Gunungkidul utilizing the theory of HVSR microtremor - Melyyanti, Meli; Nur Azis, Khafidh; Nurhanafi, Kholis (Universitas Negeri Yogyakarta, 2025)
This study aims to determine and analyze geological conditions based on the dominant frequency (fo) and amplification factor (Ao) values, determine sediment layers based on vs values, and interpret sediment thickness based on ground profiles of shear wave velocity using the ellipcity curve method in the Bribin Underground River area, Gunungkidul. This research method uses microtremors taken directly in the field with a seismic instrument that produces microtremor signal data. The results of the study produced dominant frequency (fo) values ​​ranging from 2.07 to 14.9 Hz where low frequency values ​​(<2.5 Hz) are evidenced by the presence of limestone, while amplification (Ao) values ​​range from 1.42 to 3.81 which are mostly located in the medium and high zones, with a thin surface layer of about 5 to 10 meters with sediment thickness values ​​on the north to middle side being quite thick, while the south side shows thin sediment thickness because it is located around the Underground River flow and is dominated by karst mountain areas. Thus the information obtained can be used to develop the potential of natural resources and related geological risks.